2020
DOI: 10.3171/2019.11.focus19778
|View full text |Cite
|
Sign up to set email alerts
|

Heschl’s gyrus fiber intersection area: a new insight on the connectivity of the auditory-language hub

Abstract: OBJECTIVEThe functional importance of the superior temporal lobe at the level of Heschl’s gyrus is well known. However, the organization and function of these cortical areas and the underlying fiber tracts connecting them remain unclear. The goal of this study was to analyze the area formed by the organization of the intersection of Heschl’s gyrus–related fiber tracts, which the authors have termed the “Heschl’s gyrus fiber intersection area” (HGFIA). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…As we know, verbal working memory is divided into phonological store and articulatory rehearsal (Baddeley, 1992). The Heschl gyrus is a major component of the superior temporal gyrus and forms the primary auditory region (Fernandez et al, 2020); the IFG is also considered to play an important role in auditory and visual verbal information processing (Liu X et al, 2012;Zhu et al, 2020). Therefore, these two brain regions are both related to verbal working memory, thus supporting our observations.…”
Section: Discussionsupporting
confidence: 87%
“…As we know, verbal working memory is divided into phonological store and articulatory rehearsal (Baddeley, 1992). The Heschl gyrus is a major component of the superior temporal gyrus and forms the primary auditory region (Fernandez et al, 2020); the IFG is also considered to play an important role in auditory and visual verbal information processing (Liu X et al, 2012;Zhu et al, 2020). Therefore, these two brain regions are both related to verbal working memory, thus supporting our observations.…”
Section: Discussionsupporting
confidence: 87%
“…Complementing these, are studies of intraoperative stimulation of ILF/IFOF. The majority of such studies have found IFOF stimulation to cause semantic paraphasias (Almairac et al, 2015;Duffau, 2015;2009;Fernández et al, 2020;Gil-Robles et al, 2013;Mandonnet et al, 2007;Moritz-Gasser et al, 2013;Motomura et al, 2018;2014). ILF's role is more contested; some have found ILF stimulation to cause omission errors (Herbet et al, 2019) and some have found no adverse effect on language production when stimulating this tract (e.g., Gil-Robles et al, 2013;Mandonnet et al, 2007;Moritz-Gasser et al, 2013).…”
Section: Ilf and Ifofmentioning
confidence: 99%
“…In this article, Fernández, Velásquez, García Porrero, Marco de Lucas, and Martino present converging evidence from cadaveric fiber dissections, in vivo diffusion MRI tractography, and intraoperative subcortical stimulation to describe the complex white matter architecture in the posterior region of the superior temporal lobe around Heschl's gyrus and the acoustic radiations. 5 The authors performed detailed dissections in 8 cadaveric hemispheres (4 left and 4 right). They also acquired and analyzed data from diffusion MRI probabilistic tractography in 8 control hemispheres from 4 healthy subjects and intraoperative electrical stimulation mapping in 6 patients with left temporal lobe gliomas who underwent awake resections.…”
mentioning
confidence: 99%